2020
DOI: 10.1128/jvi.01680-19
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminolysis and Glycolysis Are Essential for Optimal Replication of Marek’s Disease Virus

Abstract: Viruses may hijack glycolysis, glutaminolysis, or fatty acid β-oxidation of host cells to provide the energy and macromolecules required for efficient viral replication. Marek’s disease virus (MDV) causes a deadly lymphoproliferative disease in chickens and modulates metabolism of host cells. Metabolic analysis of MDV-infected chicken embryonic fibroblasts (CEFs) identified elevated levels of metabolites involved in glutamine catabolism, such as glutamic acid, alanine, glycine, pyrimidine, and creatine. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
0
32
1
Order By: Relevance
“…Any mitochondrial dysfunction will jeopardize melatonin production. In many cases, viruses direct the host cell metabolism to anaerobic glycolysis for their rapid replication while the cellular energy demand will be adapted to glutamine metabolism (glutaminolysis) [ 159 , 160 ]. A mechanism for this is that viruses infection triggers mitochondrial ROS production, which stabilizes hypoxia-inducible factor-1α (HIF-1α) and consequently promotes anaerobic glycolysis in COVID-19 infection [ 161 ], as known for other viruses.…”
Section: Melatonin Synthesis: a Target Of Virus Infectionmentioning
confidence: 99%
“…Any mitochondrial dysfunction will jeopardize melatonin production. In many cases, viruses direct the host cell metabolism to anaerobic glycolysis for their rapid replication while the cellular energy demand will be adapted to glutamine metabolism (glutaminolysis) [ 159 , 160 ]. A mechanism for this is that viruses infection triggers mitochondrial ROS production, which stabilizes hypoxia-inducible factor-1α (HIF-1α) and consequently promotes anaerobic glycolysis in COVID-19 infection [ 161 ], as known for other viruses.…”
Section: Melatonin Synthesis: a Target Of Virus Infectionmentioning
confidence: 99%
“…For many years, an increase in the pathogenicity of MDV strains has been observed despite immunoprophylaxis being used in day-old chicks. Such an increase was observed as early as 1997 in the vaccinated flocks of birds ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 90%
“…Only weight loss and an increase in the number of deaths among birds are observed. In the internal organs of infected birds, mainly enlargement of the liver and spleen is noted with the presence of necrotic foci in these organs ( 2 , 3 ). Virological methods (isolation in cell cultures or chicken embryos) and methods based on molecular biology principally using amplification reactions (PCR) together with their variants, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…All viral plaques were measured using the ImageJ software area tool (NIH, USA). The freehand tool was used to measure the defined plaque area (square micrometers) based on anti-gB staining as described previously ( 5 , 6 ). Data were corrected and exported as plaque size areas (square millimeters).…”
Section: Methodsmentioning
confidence: 99%
“…MDV can infect many cell types; however, latency is mainly established in CD4 + T cells, which are transformed into lymphoma cells ( 1 4 ). We have recently shown that MDV infection modulates cell metabolism and specifically enhances fatty acid synthesis and the formation of lipid droplets ( 5 , 6 ). It has been suggested that the alteration of lipid metabolism by MDV causes atherosclerosis in infected chickens ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%